The Role of Organization Commitment, Machiavellian, Auditor Performance on Dysfunctional Auditor Behavior and Audit Quality as an Intervening Factor - Salsabila Ivana Surya Putri; Ratna Mappanyukki (IAEI, 2023)
This study aims to determine the influence of the Role of Organization Commitment, Machiavellian, and Auditor Performance towards Dysfunctional Auditor Behavior. This research is quantitative research using primary data. The research method used is convenience sampling. The research data was obtained by distributing questionnaires to 106 Auditor respondents working at Public Accounting Firms registered with the OJK and located in the DKI Jakarta Area. The result showed that the role of organization commitment and auditor performance did not affect dysfunctional auditor behavior, but Machiavellian had an effect on dysfunctional auditor behavior. The role of organization commitment and Machiavellian had a significant positive effect on mediated dysfunctional auditor behavior by audit quality, while auditor performance had no effect on dysfunctional auditor behavior mediated by audit quality.